Near-term pregnant women in the Dominican Republic experience high rates of Group B Streptococcus rectovaginal colonization with virulent strains. - Katherine M Laycock; Francia Acosta; Sandra Valera; Ana Villegas; Elia Mejia; Christian Mateo; Rosa Felipe; Anabel Fernández; Megan Job; Sophia Dongas; Andrew P Steenhoff; Adam J Ratner; et al. (Public Library of Science (PLoS), 2023)
Maternal colonization with Group B Streptococcus (GBS) is an important cause of stillbirth, prematurity, and serious infection and death in infants worldwide. Resource constraints limit prevention strategies in many regions. Maternal GBS vaccines in development could be a more accessible prevention strategy, but data on geographic variations in GBS clones are needed to guide development of a broadly effective vaccine. In the Dominican Republic (DR), limited data suggest that pregnant women experience GBS colonization at rates among the highest globally. We aimed to determine the prevalence of maternal rectovaginal GBS colonization and describe clonal characteristics of colonizing strains in the DR. A cross-sectional study assessed rectovaginal GBS colonization in 350 near-term pregnant women presenting for routine prenatal care at an urban tertiary center in the DR. Rectovaginal samples were tested with chromogenic Strep B Carrot Broth and cultured for confirmatory whole-genome sequencing. In a secondary analysis, participants' demographics and histories were assessed for association with GBS colonization. Rectovaginal GBS colonization occurred in 26.6% of women. Serotypes Ia, Ib, II, III, IV, and V were detected, with no one serotype predominating; serotype III was identified most frequently (21.5%). Virulent and emerging strains were common, including CC17 (15.1%) and ST1010 (17.2%). In this first characterization of maternal GBS serotypes in the DR, we found high rates of rectovaginal colonization including with virulent and emerging GBS strains. The serotypes observed here are all targeted by candidate hexavalent GBS vaccines, suggesting effective protection in the DR.